PSYCHOLOGICAL DIFFERENCES BETWEEN CHILDREN WITH MANY CHILDREN IN A FAMILY AND ONLY CHILDREN (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Adolescents from families with different children are all considered leaders in solving problems, but their methods are different. While adolescents from large families are based on cooperation and mutual understanding, adolescents with only one child require support from those around them.